PQ monitor-based automated fault location using database technique for 11kV distribution system - Tan C.K.; Ramachandaramurthy V.K. (Praise Worthy Prize S.r.l, 2023)
Various fault locating techniques have been thoroughly discussed throughout the decades. Many of the techniques prior to this require many monitors and also relay operation information to accurately locate the fault. The latest fault locating approach utilizes power quality (PQ) monitors, which are faster and able to detect any short duration events. Majority of the fault locating techniques however focuses on locating downstream faults only. This paper proposes a novel technique to locate faults in several neighboring substations utilizing only one PQ monitor, thus breaking the boundaries of conventional downstream fault locating techniques. Besides locating faults in neighboring substations, this technique also allows the type of fault to be identified. The algorithm uses Three-Dimension (3D) Voltage Vector Database Matching method to accomplish this task. The algorithm proposed in this paper can accurately point to the fault location. Successful identification of fault location using this proposed technique will allow engineers to identify incipient faults in the substation. This will certainly revolutionize the way engineers plan and execute their substation maintenance strategy. 2011 Praise Worthy Prize S.r.l. - All rights reserved.